2010
DOI: 10.1002/jmv.21749
|View full text |Cite
|
Sign up to set email alerts
|

Association between human papillomavirus infection and laryngeal squamous cell carcinoma

Abstract: The aim of this study was to compare the prevalence of human papillomavirus (HPV) infection in laryngeal squamous cell carcinoma using two methods: PCR-DNA enzyme immunoassay (PCR/DEIA) and immunohistochemistry (IHC) for detection of HPV in specimens of laryngeal squamous cell carcinoma and to correlate the presence of HPV with the epidemiological and clinicopathological features of recurrence and survival. HPV DNA was amplified from 93 paraffin-embedded laryngeal squamous cell carcinoma tissue specimens by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0
7

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 25 publications
5
62
0
7
Order By: Relevance
“…Only data generated from primary squamous cell carcinomas (SCC) were extracted, and we excluded reports if: (1) the detection methods were not well-detailed, and/or (2) HPV data could not be extracted per anatomic site. We took care to avoid tallying overlapping patient cohorts [2][3][4][5][6][7][8][9][10][11][12][13]. The final extracted data included: county, year of publication, anatomical site, HPV type, detection method of including primers, and summary of findings for cancers, patient controls, benign lesions, potentially premalignant lesions, and premalignant lesions, when available.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Only data generated from primary squamous cell carcinomas (SCC) were extracted, and we excluded reports if: (1) the detection methods were not well-detailed, and/or (2) HPV data could not be extracted per anatomic site. We took care to avoid tallying overlapping patient cohorts [2][3][4][5][6][7][8][9][10][11][12][13]. The final extracted data included: county, year of publication, anatomical site, HPV type, detection method of including primers, and summary of findings for cancers, patient controls, benign lesions, potentially premalignant lesions, and premalignant lesions, when available.…”
Section: Methodsmentioning
confidence: 99%
“…Compared to oral carcinomas, a greater diversity of other HPV types has been detected: HPV18, HPV26, HPV31, HPV33, HPV39, HPV36, HPV45, HPV51, HPV52, HPV58, HPV59, HPV66, and HPV69 [8,9,14,20,26,29,39,65,71,90,94]. Low-risk HPV are uncommonly detected, and might represent incidental ''bystander'' rather than possibly ''driver'' infection [29,39,65,75,90,94].…”
Section: Hpv and Cancers Of The Larynxmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have reported an association between HPV and HNSCC of the larynx [8,9] and other subsites [7]. Methods for testing tumor tissue for HPV are not standardized [10] and, moreover, there is little consensus on optimal treatment for HPV-associated HNSCC.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, in 1994, Clayman et al also showed that HPV detection significantly correlated with decreased survival (Clayman et al, 1994). On the other hand, other studies have failed to demonstrate an association between HPV positivity and prognosis (Duray et al, 2011a;Ernoux et al, 2011;Koskinen et al, 2003;Morshed et al, 2010). From a biological point of view, it is difficult to explain why patients with HPV infections have a worse survival than HPV-negative patients.…”
Section: Prognosis Of Hpv Positive Head and Neck Squamous Cell Carcinomamentioning
confidence: 99%